Characterization of Fe2O3/Mn2O3 Oxygen Carrier for Chemical Looping Combustion Prepared by Dry Impregnation Method - Afandi, Nurfanizan Mohd; Abd Manap, Abreeza Noorlina; Mansor, Fitri Hanif; Abdul Ghani, Mohammad Firdaus; Kadir, NF; Liu, Wen (International Journal of Engineering and Technology, 2018)
Recently, bauxite waste was found as newly sourced of Fe-based oxygen carrier in chemical looping combustion (CLC) since it contains high Fe and capable to be used as oxygen carrier at low cost. This study focuses on synthesizing and characterizing the bauxite waste that found in Malaysia with Mn2O3 using dry impregnation method and study the feasibility of this bauxite waste as oxygen carrier. Results show the combination of bauxite waste – Mn2O3 at 900°C produces crystallite size 21 nm with the presence of Fe-Mn, stable Al2O3 and Ti elements that can improve the reactivity of Fe-Mn oxygen carrier. Moreover, Al2O3 that contains naturally in bauxite waste can acts as supported material for Fe-Mn oxygen carrier in order to increase performance in CLC process. Therefore, this powder was successfully synthesized using dry impregnation method at calcination temperature 900°C and fit to be tested in a fluidized bed reactor to simulate the CLC process since it has smaller and stable particle size.